IADC/SPE Asia Pacific Drilling Technology Conference and Exhibition 2010
DOI: 10.2118/135904-ms
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Wellbore-Drilling Instability in Naturally Fractured Rock Formations with Field Applications

Abstract: Overcoming wellbore drilling instability in fractured-rock formations always presents one of the major challenges to drilling engineers. Due to different fluid-diffusion rates and compressibility degrees between the rock's matrix and fracture network, there are two distinct pore-pressure fields and subsequently different effective stresses developed in a saturated fractured formation. It is recognized that wellbore instabilities such as collapses are caused by excessive effective stress concentrations at or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Formation microscanner images and scanning electron microscopy images revealed that both macroand microscale fractures and fissures within the shale matrix can be recognized [18]. The presence of the discontinuity surfaces (i.e., fractures) in shale for mations has been noted using wellbore imaging techniques.…”
Section: Introductionmentioning
confidence: 97%
“…Formation microscanner images and scanning electron microscopy images revealed that both macroand microscale fractures and fissures within the shale matrix can be recognized [18]. The presence of the discontinuity surfaces (i.e., fractures) in shale for mations has been noted using wellbore imaging techniques.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, the bedding planes and natural fractures can propagate due to lost circulation. Lost circulation can cause the decrease of borehole pressure and the damage of wall surrounding rock and then induces the collapse of wellbore [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Following the invasion of water through the nanopore throats into the shale formation weakens the wellbore and leads to problems such as a stuck pipe and hole collapse. [5][6][7] The solution to this problem is to engineer a nano uid loss agent in the drilling uid to plug the nanopores of shale and shut off the loss of water. As showed in Fig.…”
Section: Introductionmentioning
confidence: 99%